Analisis Pemasaran Syariah dalam Meningkatkan Penjualan Produk (Studi Kasus Wima Aesthetic Syar'i Skincare, Pemalang): Analisis Pemasaran Syariah dalam Meningkatkan Penjualan Produk (Studi Kasus Wima Aesthetic Syar'i Skincare, Pemalang) - Achmad Fajaruddin; Abdi Rahayu, Yogi Suryaningsih (ITB AAS INDONESIA Surakarta, 2025)
Business is an activity that requires skill and seriousness. One of the business units is the beauty industry. The beauty industry is a dynamic and constantly innovating industry, with rapid development and increasingly fierce competition. Beauty industry entrepreneurs need to improve and develop marketing strategies to face competition. One of the marketing strategies that can be used is sharia marketing, this is relevant because today more and more consumers are looking for products and services that are in accordance with Islamic values. Wima Aesthetic Syar'i Skincare is a sharia-based beauty clinic that has implemented Islamic principles in all its operational activities. The sharia marketing strategy implemented is one of the company's efforts to increase sales of its goods and services. The purpose of this study is to determine the sharia marketing strategy applied by Wima Aesthetic Syar'i Skincare in increasing product sales as well as the effectiveness and efficiency of the sharia marketing strategy carried out. The method used in this research is a qualitative approach with descriptive methods. Data collection techniques through observation, interviews and documentation. The data analysis used is triangulation which includes data reduction, data presentation and conclusion drawing. The results of this study indicate that the sharia marketing strategy applied by Wima refers to the marketing mix (4P) product, price, place and promotion which is integrated with the characteristics of sharia marketing rabbaniyah, akhlaqiyah, waqi'iyah and insaniyah. By applying the principles of sharia marketing can increase sales of Wima products by 10-15% every month as measured by sales volume, profit and company growth. In addition, the application of sharia marketing is not only concerned with company profits but consumers and the surrounding community. This can certainly increase public awareness and trust in Wima.